Social and Cultural Barriers to the Empowerment of Yemeni Women in Public Employment (An Analytical Field Study) - Abbas, Fatima Ali Abdullah (Arab Journal for Sciences and Research Publishing, 2025)
This study aims to analyze the key social and cultural barriers that limit the empowerment of Yemeni women in public employment, with a focus on traditions, community perceptions, and the role of family. A descriptive-analytical methodology was employed, utilizing official data from the Ministry of Civil Service along with surveys and interviews conducted with 120 women across Sana’a, Taiz, and Aden.Results indicate that women constitute only 29% of public employees, with a high avoidance of roles requiring travel or night shifts due to social and familial pressures. The study also reveals limited promotion opportunities, unequal access to training programs, and structural bias in recruitment and evaluation processes.The research recommends activating equal opportunity policies, launching national awareness campaigns to challenge gender stereotypes, and allocating a fixed quota of public jobs for women. Additionally, it calls for restructuring workplace environments to better support women, especially in rural areas.
Keywords: Women empowerment; public employment; social barriers; gender equality; Yemen